Kontroverse Unterkelchstein: kontrollieren oder intervenieren? = Controversy on lower pole stones. Monitor or intervene? - Häcker, Axel; Michel, Maurice Stephan (Der Urologe, 2012)
For many years, the treatment options of lower pole stones have been discussed controversially: Watchful waiting, shock wave lithotripsy, flexible ureterorenoscopy and percutaneous litholapaxy. Small lower pole stones <1 cm can be monitored actively. Shock waves can disintegrate the stones and are recommended for stones <1 cm. However, the stone-free rate is limited because of the particular anatomy of the lower pole. Modern flexible ureterorenoscopes can nowadays reach even anatomically unfavourable lower calyxes. For stones <1 cm good stone-free results can be achieved. For larger stones >2 cm percutaneous nephrolithotomy (PNL) is the standard treatment modality.